‘Liberdade, Igualdade, Fraternidade ou a Morte?’: extravios do post(al) colonial em Nação Crioula - Gonçalves Miranda, Rui (Universidade de São Paulo (Brazil), 2014)
This article aims to contest oedipal readings and the emphasis on symbols (utopian, heterotopian) which reduce the pluridimensionality of the "Postal" AND "Postal Politics" (BENNINGTON) on creole's (Post-/Neo)colonial spacing of the South Atlantic. A "Destinerrant" (DERRIDA) reading will seek to expose the constitutive impropriety of any "communitarian" projection and appropriation (ESPOSITO), beyondthe (de)limitations of predestined correspondences and triangulations.